Factors associated with neonatal near miss in a Midwest capital in Brazil - Priscilla Shirley Siniak dos Anjos Modes; Maria Aparecida Munhoz Gaíva; Amanda Cristina de Souza Andrade; Lenir Vaz Guimarães (Instituto Materno Infantil de Pernambuco, 2023)
Abstract Objectives: to estimate neonatal near miss rates and investigate sociodemographic, obstetric, childbirth, and neonate factors residing in a Midwest capital city. Methods: observational cohort study of live births from Cuiabá in the period of 2015 to 2018, with data from the Sistemas de Informações sobre Mortalidade e sobre Nascidos Vivos (Mortality and Live Birth Information Systems). The neonatal near miss rate was calculated according to sociodemographic, obstetric, childbirth, and neonate variables. Logistic regression model was adjusted to analyze the factors associated with neonatal near miss. Results: the neonatal near miss rate was 22.8 per thousand live births and the variables showed an association with the outcome were: maternal age 35 years or older (OR=1.53; CI95%=1.17-2.00), having fewer than six prenatal consultations (OR=2.43; CI95%=2.08-2.86), non-cephalic fetal presentation (OR=3.09; CI95%=2.44-3.92), multiple pregnancy (OR=3.30; CI95%=2.57- 4.23), no live birth (OR=1.62; CI95%=1.34-1.96) or one live birth (OR=1.22; CI95%=1.00-1.48), delivery in public/university hospital (OR=2.16; CI95%=1.73-2.71) and philanthropic hospital (OR=1.51; CI95%=1.19-1.91) and non-induced labor (OR=1.50; CI95%=1.25-1.80). Conclusion: the neonatal near miss rate was 3.04 cases for each death, and neonatal near miss was influenced by maternal characteristics, obstetric history, type of birth hospital, and delivery care organization.